Encephalopathy in Preterm Infants: Advances in Neuroprotection With Caffeine - Yang, Liu; Yu, Xuefei; Zhang, Yajun; Liu, Na; Xue, Xindong; Fu, Jianhua (Frontiers in Pediatrics, 2021)
With the improvement in neonatal rescue technology, the survival rate of critically ill preterm infants has substantially increased; however, the incidence of brain injury and sequelae in surviving preterm infants has correspondingly increased. Although the etiology and pathogenesis of preterm brain injury and its prevention and treatment have been of concern in recent years, powerful and effective neuroprotective strategies are lacking. Caffeine is an emerging neuroprotective drug, and its benefits have been widely recognized; however, its effects depend on the dose of caffeine administered, the neurodevelopmental stage at the time of administration, and the duration of exposure. The main mechanisms of caffeine involve adenosine receptor antagonism, phosphodiesterase inhibition, calcium ion activation, and γ-aminobutyric acid receptor antagonism. Studies have shown that the beneficial effects of caffeine on the immature brain are direct and indirect. Accordingly, this article briefly reviews the pharmacological characteristics of caffeine, its mechanism of action in the context of encephalopathy in premature infants, and its use in the neuroprotection of encephalopathy in this patient population.